1995
DOI: 10.1097/00000658-199504000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intrapancreatic Trypsinogen Activation in Ischemia-Induced Experimental Pancreatitis

Abstract: ObjectiveThe potential of pancreatic ischemia to cause acute pancreatitis as indicated by morphologic changes and ectopic trypsinogen activation was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 29 publications
4
32
0
1
Order By: Relevance
“…Interstitial trypsinogen activation is accepted as an early event in acute pancreatitis and plays a role in the progression to necrotizing pancreatitis [2, 4, 24, 25, 26]. In our study, high concentrations in pancreatic necroses and ascites but low values in pancreatic abscess and pleural effusion underline the role of local trypsinogen activation in the development of pancreatic necroses.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Interstitial trypsinogen activation is accepted as an early event in acute pancreatitis and plays a role in the progression to necrotizing pancreatitis [2, 4, 24, 25, 26]. In our study, high concentrations in pancreatic necroses and ascites but low values in pancreatic abscess and pleural effusion underline the role of local trypsinogen activation in the development of pancreatic necroses.…”
Section: Discussionsupporting
confidence: 61%
“…In previous studies, trypsinogen activation has been shown to be an important pathophysiologic factor in the progression of pancreatic inflammation to necrotizing pancreatitis [2, 4, 24, 25, 26, 27]. Active trypsin is difficult to measure because is it quickly complexed or denatured.…”
Section: Discussionmentioning
confidence: 99%
“…This cellular acidosis increases the potential for cathepsin B, which has a pH optimum of 3.8, to activate trypsinogen intracellularly [106]. Within the pancreas, this mechanism may explain the presence of activated extraluminal trypsin as a very early event in the pathogenesis of AP [107, 108]. Indeed, after hemorrhagic shock, studies directed at intracellular changes in acinar cells demonstrated marked cellular vacuolization, increased lyosomal size and fragility, and cell disruption [109].…”
Section: Ischemia/reperfusion Injury Of the Pancreasmentioning
confidence: 99%
“…A key step for initiating many forms of pancreatitis appears to be the pathological intracellular activation of digestive zymogens (15). In vivo studies that use supramaximal concentrations (10-to 100-fold greater than that generating a maximal secretory response) of CCK or cholinergic agonists generate acute pancreatitis (9) and zymogen activation (18). Likewise, hyperstimulation of isolated pancreatic acini by CCK leads to the rapid activation of proteases and enhanced zymogen processing (15).…”
mentioning
confidence: 99%